May Sinclair’s Literary Criticism: A Commitment to Modernity - Isabelle BRASME (E-REA)
Although May Sinclair’s work has tended to be relegated to the periphery of modernism, Sinclair entertained close relationships with many major modernist figures such as Ford Madox Ford, Ezra Pound, and Rebecca West. A prolific novelist, Sinclair also wrote extensively on ways in which literature could participate in the modern movement, from the Brontë sisters to the Imagist poets, and is perhaps best known for first applying William James’s metaphor of the “stream of consciousness” to literary technique in her analysis of Dorothy Richardson’s first three instalments of Pilgrimage. Additionally, Sinclair’s intensely personal and dynamic critical style is itself a mindful exercise in a more innovative approach to criticism that proves akin to the modernist works that she tackles. Lastly, Sinclair’s criticism of her fellow modernist writers gives us a better insight into the innovation present in Sinclair’s own literary works, and into her career’s trajectory as it moved away from traditional realism to psychological realism. Examining Sinclair’s critical work thus allows us to establish the specificity of her perspective on modernist practices of writing and to re-examine the canons of modernism against the grain of what came to be the accepted definition of avant-garde writing.